Characterization of Hydroxyapatite Material from Bovine for Making 3D Printer Filament Method Fused Deposition Modelling for Implants Scaffolds Mandibular Reconstruction - Solechan -; Saifudin Ali Anwar (Universitas Muhammadiyah Semarang, 2016)
Abstract. Bone disease caused cancer by the WHO in 2008 reached 12 million new cancer cases, 7 million people diedand 5 million people living with cancer. Bone tumors part of cancer, the case is less than 1% of all cancers. Location ofthe tumor at most ditibia 41%, femur bone at most 33%, maxillofacial and mandibular bone 3%. Mandible cancer treatment using scaffolds for bone recovery. Scaffolds made of polymers, ceramics and composites. Now these scaffolds formed with a 3D print through the filament composite. Material filament composite with filler hidroxyapatite bovine (HAb) or hidroxyapatite from cow bones have more strength. The method of making bovine Hidroxyapatite from cow bone cortical portion with calcination process at a temperature of 1100 o C with a hold time of 3 hours. HAb material characterization test results are the functional groups and the diffractogram peaks sharp strengthen Hab has in commonn with commercial HA. HAb material has a ratio of Ca/P 2:15 while commercial HA 1.67. Material Hab has more calcium element of commercial HA. HAb grain shape irregular-shaped box with a grain size of 300 nm, making it suitable to be used as a filler material composite filament print 3D.